Nuprl Lemma : hdf-until-ap-snd
∀[A,B,C:Type]. ∀[X:hdataflow(A;B)]. ∀[Y:hdataflow(A;C)]. ∀[a:A]. ((snd(hdf-until(X;Y)(a))) = (snd(X(a))) ∈ bag(B))
Proof
Definitions occuring in Statement :
hdf-until: hdf-until(X;Y)
,
hdf-ap: X(a)
,
hdataflow: hdataflow(A;B)
,
uall: ∀[x:A]. B[x]
,
pi2: snd(t)
,
universe: Type
,
equal: s = t ∈ T
,
bag: bag(T)
Lemmas :
bag_wf,
pi2_wf,
hdf-until-ap,
hdf-ap_wf,
iff_weakening_equal,
bag-null_wf,
bool_wf,
eqtt_to_assert,
assert-bag-null,
eqff_to_assert,
equal_wf,
bool_cases_sqequal,
subtype_base_sq,
bool_subtype_base,
assert-bnot,
equal-wf-T-base,
hdataflow_wf
\mforall{}[A,B,C:Type]. \mforall{}[X:hdataflow(A;B)]. \mforall{}[Y:hdataflow(A;C)]. \mforall{}[a:A].
((snd(hdf-until(X;Y)(a))) = (snd(X(a))))
Date html generated:
2015_07_17-AM-08_06_09
Last ObjectModification:
2015_02_03-PM-09_46_39
Home
Index